Examining the Level of Environmental Consciousness Across Socio-Demographics: A Pathway to Sustainable Consumption for Coir Composite Furniture in Emerging Economy - Gayathri RAMESH (Communications of International Proceedings, 2025)
Sustainable consumption behavior towards products and class of products is well defined and well established. The main objective of the study is to understand the influence of socio-demographic factors on environment consciousness among individuals and analyze the components factors which have a bearing on environment consciousness. The sample respondents are individual users of   Coir Composite Furniture across various organizations. The method used for data collection is face-to-face interview using a structured questionnaire. In total 260 respondents participated in the survey across the states of Karnataka and Kerala in India. The study incorporates the strengths of multiple regression analysis, factor analysis and multivariate analysis of variance. The results indicated that the level of environment consciousness is high among individuals across different organisations in India. This research demonstrates that retailers may create effective marketing programmes and tactics to positively influence potential customers to direct their attention to environmentally friendly purchases.
Keywords: Sustainable Consumption; Environment consciousness; socio-demographics; Coir Composite Furniture; Organisations.